Measurement of Soil Radon activity in Bakreswar-Tantloi region - Arkajit Aich (PANGAEA, 2021)
Bakreswar-Tantloi region of India, famous for the abundance of Hot Springs in the area is geothermally active and therefore of high interest to explore the possibility of setting up a non-conventional Energy base. Studying the composition of spring-gas and soil-gas of the area is an active area of research aimed to properly understand the local geology and potential of the region. Besides, the measurement of anomalies in concentrations of Radon in soil and groundwater can be used as earthquake precursor (Friedmann 2012; doi:10.1093/rpd/ncr229) and there is ongoing effort to monitor Radon concentrations at different places of the world to study the correlations. In this work, the Radon content in soil-gas has been measured in 41 specific geographic locations spread out across the region of interest. The measurements were taken in the year 2017 around the months of January-April in the daytime. Radon is a radioactive component of soil gas and hence its relative abundance in Soil-gas of a region can be estimated by measuring the corresponding radioactivity. A battery or net-operated device known as Alphaguard, which is capable of measuring radon-activity of air or water (depending upon how the device is set up) was utilized for taking the measurements. Soil Radon activity was monitored in the sites of interest for about 40 minutes - 1 hour and then averaged out. The dataset chiefly comprises of the latitude and longitude of the locations, and the measured (average) radon-activity per unit volume of soil-gas of the respective locations. Mean Radon activity in the region was found to be 16.50 kBq/m^3 with the standard deviation of the sample set of 13.62 kBq/m^3.